2014
DOI: 10.1002/hep.26894
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome proliferator-activated receptor α activates human multidrug resistance transporter 3/ATP-binding cassette protein subfamily B4 transcription and increases rat biliary phosphatidylcholine secretion

Abstract: Multidrug resistance transporter 3/ATP-binding cassette protein subfamily B4 (MDR3/ABCB4) is a critical determinant of biliary phosphatidylcholine (PC) secretion. Clinically, mutations and partial deficiencies in MDR3 result in cholestatic liver injury. Thus, MDR3 is a potential therapeutic target for cholestatic liver disease. Fenofibrate is a peroxisome proliferator-activated receptor (PPAR) α ligand that has antiinflammatory actions and regulates bile acid detoxification. Here we examined the mechanism by w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 41 publications
5
56
0
Order By: Relevance
“…Of interest for therapy of cholangiopathies, fibrates stimulated the transcription and canalicular insertion of the phospholipid export pump MDR3/ABCB4 [132,133] , thereby facilitating the formation of mixed micelles in bile via increase in phosphatidylcholine and renders bile less toxic [133,134] . This finding was supported by the studies showing PPARα binding to response elements in the MDR3 promoter [135] . Functional evidence for fibrateinduced MDR3 activation was provided by increase in biliary phospholipid excretion in patients undergoing a percutaneous trans-hepatic biliary drainage after bezafibrate treatment [136] .…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorssupporting
confidence: 78%
“…Of interest for therapy of cholangiopathies, fibrates stimulated the transcription and canalicular insertion of the phospholipid export pump MDR3/ABCB4 [132,133] , thereby facilitating the formation of mixed micelles in bile via increase in phosphatidylcholine and renders bile less toxic [133,134] . This finding was supported by the studies showing PPARα binding to response elements in the MDR3 promoter [135] . Functional evidence for fibrateinduced MDR3 activation was provided by increase in biliary phospholipid excretion in patients undergoing a percutaneous trans-hepatic biliary drainage after bezafibrate treatment [136] .…”
Section: Bile Acids Receptors and Other (Nuclear Hormone) Receptorssupporting
confidence: 78%
“…However, potential involvement of PPARa and LXR in CYP3A4 repression by GW4064 appears unlikely. Our results from human hepatocytes indicate that GW4064 does not alter the mRNA expression of the representative target genes of these nuclear receptors, including MDR3 (Ghonem et al, 2014), FASN, and SREBF1 (Wagner et al, 2003) (data not shown). Inflammation is also known to alter CYP3A4 expression; CYP3A4 expression is downregulated in the state of inflammation (Aitken et al, 2006).…”
Section: Discussionmentioning
confidence: 74%
“…The anticholestatic effect of fibrates is linked to a direct control of the multidrug resistance protein 3 (MDR3 or ABCB4) gene expression by PPARα [49,50]. Indeed, activation of PPARα leads to increased phosphatidylcholine excretion in vitro [50], suggesting a protective mechanism against bile toxicity in vivo. Furthermore, PPARα may limit bile acids deleterious effects by decreasing CYP7A1 expression, while increasing CYP3A4 expression [49].…”
Section: Nrs In Liver Pathophysiologymentioning
confidence: 99%
“…Activation of PPARs with fibrates has anticholestatic activity in patients with PBC under UDCA therapy [49]. The anticholestatic effect of fibrates is linked to a direct control of the multidrug resistance protein 3 (MDR3 or ABCB4) gene expression by PPARα [49,50]. Indeed, activation of PPARα leads to increased phosphatidylcholine excretion in vitro [50], suggesting a protective mechanism against bile toxicity in vivo.…”
Section: Nrs In Liver Pathophysiologymentioning
confidence: 99%